On some species of Chone Krøyer, 1856 (Polychaeta: Sabellidae) from world-wide localities - Tovar-Hernández, María Ana (Zootaxa, 2007)
The present study deals with the revision of type and non-type material from species of Chone Krøyer, 1856 (Polychaeta: Sabellidae) that have been described from world-wide isolated localities. Chone australiensis Hartmann-Schröder, 1979, C. fauveli McIntosh, 1916, C. kroyerii Sars, 1862, C. letterstedti (Kinberg, 1867), C. murmanica Lukasch, 1910, C. normani McIntosh, 1916, C. paracincta Hartmann-Schröder, 1962, and C. rosea Hartmann-Schröder, 1965, are redescribed. Two additional forms are recognized as independent taxa, referred to as Chone sp. “Aleutian Islands” and Chone sp. “British Virgin Islands”. These species are informally described since few specimens are available; however, they are included here in order to facilitate and encourage further research. Sabella costulata Grube, 1877, is transferred to Chone. Chone suspecta Krøyer, 1856, is synonymized with Chone infundibuliformis Krøyer, 1856; the name infundibuliformis has priority over suspecta. Chone murmanica oculata Annenkova, 1952, deserves specific status. Chone eniwetokensis (Reish, 1968) is returned to the original genus (Euchone). Chone perseyi Zenkewitsch, 1925, and Chone rubrocincta Sars, 1862, are transferred to Euchone. Chone reayi McIntosh, 1916, is transferred to Jasmineira Langerhans, 1880. Differences and similarities with members of Euchone Malmgren, 1866, and close genera are discussed.